Movement of Goods in Canada: A State-of-the-Art Review and a Grounded Theory Investigation of Perceived Barriers - Sears, Sean (My University, 2020)
This twofold work first presents a state-of-the-art review of the roots and context for freight mobility barriers, and secondly investigates the key barriers to freight mobility in Canada from the perspective of stakeholders. The review provides a holistic approach to understanding the interconnected nature of mobility, spatial structure, congestion, supply chains, and the economy on generating, demanding, and hindering freight movements. The investigation develops a novel theory grounded in the experiences of stakeholders following the Strauss/Corbin extended Grounded Theory approach of symbolic interactionism. From interviews with 28 industry and government stakeholders, a total of 50 themes emerged as barriers. These barriers were grouped into four categories which frame the issue of freight mobility as being impacted by high infrastructure utilization, cost impacts of diminishing distribution reliability, rapidly growing regions and ineffective or absent policy support, and lacking a robust data collection, analysis, and sharing framework. The categories were considered in the frame of addressing goods movement barriers and were argued to be influenced by factors of cost, political risk, implement-ability, and maintainability. A framework was developed by integrating the emergent categories and factors, identifying four high-level interventions: data and knowledge mobilization; public-private collaborative freight evaluations; government funding and political support; and, capacity alterations: improvements and expansions. Overall, the key concepts of the emergent theory are to collect and analyze data to inform public-private stakeholder evaluations of policy interventions, with government funding to support both knowledge generation efforts, policy actions and capacity investments. There is a significant need to expand data collection and information sharing to enable firms and government to address physical and policy barriers which impede the effective goods movements, including infrastructure and land use planning. The theory is generally consistent with barriers identified internationally.
PERCEIVED BARRIERS TO FREIGHT MOBILITY IN CANADA
Keywords: Freight; Logistics; Canada; Grounded Theory; GT; Congestion; Freight Mobility; Last Mile; Qualitative Methods